Significados de la ciudadanía en las «sociedades no-salariales». Una mirada desde América Latina - Braz de Aquino, Cássio Adriano; Sandoval Moya, Juan (Cuadernos de Relaciones Laborales, 2002)
The purpose of this article is to discuss an analytical standpoint from where to understand the factors associated with the development of citizenship in Latin American societies. The main point is that Latin American societies haven’t followed neither the phase of economic growth, nor the cultural and political processes that have sustained the consolidation of the European well fare state. Therefore, the development of Latin American citizenship should be understood from another perspective, different from those that come from the ‘salary society’ which could help analyses how stablishes links with other material and symbolic practices involved in the performance and development of citizenship.
Keywords: Citizenship; work; Welfare State; sotial insertion; social exclusion